Hallmarks of the relationship between host and Trypanosoma cruzi sulfated glycoconjugates along the course of Chagas disease - Soprano, Luciana L.; Ferrero, Maximiliano R.; Jacobs, Thomas; Couto, Alicia S.; Duschak, Vilma G. (Frontiers in Cellular and Infection Microbiology, 2023)
American Trypanosomiasis or Chagas disease (ChD), a major problem that is still endemic in large areas of Latin America, is caused by Trypanosoma cruzi. This agent holds a major antigen, cruzipain (Cz). Its C-terminal domain (C-T) is retained in the glycoprotein mature form and bears several post-translational modifications. Glycoproteins containing sulfated N-linked oligosaccharides have been mostly implicated in numerous specific procedures of molecular recognition. The presence of sulfated oligosaccharides was demonstrated in Cz, also in a minor abundant antigen with serine-carboxypeptidase (SCP) activity, as well as in parasite sulfatides. Sulfate-bearing glycoproteins in Trypanosomatids are targets of specific immune responses. T. cruzi chronically infected subjects mount specific humoral immune responses to sulfated Cz. Unexpectedly, in the absence of infection, mice immunized with C-T, but not with sulfate-depleted C-T, showed ultrastructural heart anomalous pathological effects. Moreover, the synthetic anionic sugar conjugate GlcNAc6SO3-BSA showed to mimic the N-glycan-linked sulfated epitope (sulfotope) humoral responses that natural Cz elicits. Furthermore, it has been reported that sulfotopes participate via the binding of sialic acid Ig-like-specific lectins (Siglecs) to sulfosialylated glycoproteins in the immunomodulation by host–parasite interaction as well as in the parasite infection process. Strikingly, recent evidence involved Cz-sulfotope-specific antibodies in the immunopathogenesis and infection processes during the experimental ChD. Remarkably, sera from chronically T. cruzi-infected individuals with mild disease displayed higher levels of IgG2 antibodies specific for sulfated glycoproteins and sulfatides than those with more severe forms of the disease, evidencing that T. cruzi sulfotopes are antigenic independently of the sulfated glycoconjugate type. Ongoing assays indicate that antibodies specific for sulfotopes might be considered biomarkers of human cardiac ChD progression, playing a role as predictors of stability from the early mild stages of chronic ChD.